Smart two‐dimensional material‐based time modulated array for RFID applications. Issue 15 (9th November 2017) - Aldrigo, Martino; Masotti, Diego; Dragoman, Mircea
Abstract : In this study, the authors present an original way to combine two promising technologies: time‐modulated arrays (TMAs) and two‐dimensional (2D) materials. The potentialities of TMAs are strongly enhanced by the exploitation of 2D‐based radiators, in particular, molybdenum disulphide (MoS2 ). The great ON/OFF ratio of MoS2 under the application of low bias voltages (up to 5 V in the case of monolayer materials) would allow creating antenna arrays with switching properties, i.e. selecting just a few of the array elements to radiate. This would represent a further degree of freedom in beam‐forming for wireless engineering applications. The proposed 2D‐TMA finds an application in high‐frequency RFID technology combined with wireless sensor networks. Throughout the study, the authors will show the benefits obtained from merging TMAs and 2D materials technology; furthermore, the authors will provide some experimental results on multi‐layer MoS2 characterisation and a theoretical prediction of the link budget performance in a RFID link. Both simulation and material measurement results are encouraging, opening the path to further research in high‐performance sensing networks that exploit the most innovative results in the domain of materials engineering.